Systematization technical liquids - Іванова, Г.В.; Кумейко, О.В.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2006)
Expedient the detailed study and ordering of the nomenclature, assortment, technical requirements, physicochemical and operational properties of all groups of technical liquids is considered, considering each group separately.